Effects of Nozzle Diameter on Diesel Spray Flames: A numerical study using an Eulerian Stochastic Field Method. (December 2017) - Pang, Kar Mun; Jangi, Mehdi; Bai, Xue-Song; Schramm, Jesper; Walther, Jens Honore
Abstract: The present numerical study aims to assess the performance of an Eulerian Stochastic Field (ESF) model in simulating spray flames produced by three fuel injectors with different nozzle diameters of 100 µm, 180 µm and 363 µm. A comparison to the measurements shows that although the simulated ignition delay times are consistently overestimated, the relative differences remain below 28%. Furthermore, the change of the averaged pressure rise with respect to the variation of nozzle diameter is captured by the model. The simulated flame lift-off lengths also agree with the measurements, with a maximum relative difference of 13%. The spray flame produced by a larger nozzle diameter has a fuel-richer premixed core region despite the longer lift-of length, indicating that the higher fueling rate used with the larger nozzle diameter is a more dominating factor than the lift-off length is in influencing the air entrainment into the upstream of the spray flames. In addition, the simulated normalised flame lengths are found to decrease when the nozzle diameters increase. These predictions are in good qualitative agreement with the experimental observation. This work proves that the ESF model can serve as an important tool for the simulation of spray flames in marine diesel engines, where fuel injectors with different nozzle diameters are applied for pilot and main injections.